Pemanfaatan Mini Nutrition Assessment-Short Form (MNA-SF) untuk Mengidentifikasi Status Gizi Pasien Lansia Rawat Inap di RSUP Dr Sardjito Yogyakarta: Pemanfaatan Mini Nutrition Assessment-Short Form untuk Mengidentifikasi Status Gizi Pasien Lansia Rawat Inap di RSUP Dr Sardjito Yogyakarta - Susetyowati, Susetyowati; Winarti, Hesti; Roselani, Ari; Handayani, Sri; Sanubari, Nadira D'mas Getare; Sholikhati, Amalia Sarah (Universitas Airlangga, 2024)
Background: Identification of nutritional status upon their admission as well as influencing factors related to changes in nutritional status during hospital treatment need to be done to prevent the risk of worsening of the patient's clinical outcomes. Objectives: This study aimed to find out the nutritional status of hospitalized elderly patients at hospital admission using the Mini Nutrition Assessment-Short Form (MNA-SF) screening tool. Methods: This study was an observational design with a cross sectional design and conducted at dr. Sardjito Yogyakarta Hospital from September-November 2021. Basic characteristic data is gathered, nutritional screening is performed using MNA-SF, and nutritional status is measured using weight, height, Mid-Upper Arm Circumferences (MUAC), calf circumference, Hand Grip Strength (HGS), total fat percentage, visceral fat, muscle mass and hemoglobin. Results: A total of 86 elderly patients, ranging in age from 60 to 80 years, were recently admitted to the hospital. The results showed the prevalence of malnutrition in the hospitalized elderly was 46.5%. According to the assessment results, malnourished elderly patients had statistically significant lower Body Mass Index (BMI) (19.4±3.1), total fat levels (20.0±10.9), visceral fat levels (4.4±4.6), muscle mass (34.4±7.7), MUAC (22.6±3.4), calf circumference (27.2±6.7) dan hemoglobin (10.7±3.2) (p<0.05). Conclusions: According to MNA-SF, half of the elderly patients in hospitals were malnourished at hospital admission. Therefore, it is crucial to evaluate the nutritional state of elderly patients as soon as they are admitted and to implement the proper nutritional therapy in order to reduce its negative effects on the patients and healthcare system.